2020
DOI: 10.1002/agj2.20370
|View full text |Cite
|
Sign up to set email alerts
|

Agronomic performance of the lignocellulosic feedstock crop energy cane in the Texas Rolling Plains

Abstract: Feedstock genetics and environment are important factors determining biomass yield of biofuel crops. Field studies were conducted to evaluate agronomic performance of four energy cane (Saccharum spp. hybrid) genotypes (TUS11-62, TUS11-58, TCP10-4928, and Ho 02-113) in the Texas Rolling Plains. In the first study, cane billets were planted in 2015 and data were collected from first (2016) and second (2017) ratoons. A second study was planted in 2016 and data were collected the same year from plant cane. Data co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 53 publications
0
11
0
Order By: Relevance
“…However, at Shorter, AL, a 4-d freeze event was reported by Sladden et al (1991), which may have resulted in reduced energycane (L 79-1002) yield the following season, although low rainfall during the growing season may have also been a factor. At Chillicothe, TX, in the Texas Rolling Plains, Pokhrel et al (2020) reported reduced emergence counts, reduced stalk height, and reduced biomass in the second ratoon crop of four energycane cultivars following the occurrence of severe freezing temperatures (−16˚C) in the preceding winter. Within a low-irrigation treatment, one of the four cultivars (TUS11-62) did not survive at all.…”
Section: Discussionmentioning
confidence: 99%
“…However, at Shorter, AL, a 4-d freeze event was reported by Sladden et al (1991), which may have resulted in reduced energycane (L 79-1002) yield the following season, although low rainfall during the growing season may have also been a factor. At Chillicothe, TX, in the Texas Rolling Plains, Pokhrel et al (2020) reported reduced emergence counts, reduced stalk height, and reduced biomass in the second ratoon crop of four energycane cultivars following the occurrence of severe freezing temperatures (−16˚C) in the preceding winter. Within a low-irrigation treatment, one of the four cultivars (TUS11-62) did not survive at all.…”
Section: Discussionmentioning
confidence: 99%
“…All plots received irrigation similar to the high irrigation treatment in Trial 1. Details of planting, irrigation, and crop management activities of both Trial 1 and 2 can be found in Pokhrel et al., 2020. A summary is provided in Table 1.…”
Section: Methodsmentioning
confidence: 99%
“…A detailed description of other field data and related methods can be found in Pokhrel et al. (2020).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure 1 summarizes the differences between energy cane and sugarcane on the stalk morphology and population. Energy cane stalk height is from 4 to 6 m, whereas sugarcane stalk is smaller, from 2 to 2.5 m [33,34]. However, the sugarcane stalk is thicker than the energy cane.…”
Section: Sugarcane Breeding For Fiber and The Energy Cane Conceptmentioning
confidence: 99%